DESAIN DAN PEMBUATAN JIG AND FIXTURE PEMBENTUK RADIUS LUAR (r = 5 – 20mm) PADA MESIN BUBUT MAXIMAT V-13 DI JURUSAN TEKNIK MESIN POLITEKNIK NEGERI MALANG - Andri Setiawan Setiawan; Rafik Djoenaidi; Martha Putri Indrayanti (Polinema Press, Politeknik Negeri Malang, 2021)
On a conventional lathe, the process of forming the outer radius on the workpiece (cylinder) can be directly carried out by installing a jig and fixture to facilitate the small-scale machining process that is applied to the tool holder (carriage) instead of the tool position. it is chisel and the holder is removed. Field surveys are needed to support the data collection process, such as the dimensions of the tool post and the distance of the feeding axis of the Maximat V-13 lathe. From this data, it will be correlated in the form of a jig and fixture design with material selection as a comparison. By involving jigs and fixtures in the practicum process, it can provide additional insight regarding work systems and time efficiency in the production process. So that it can help practitioners / students to recognize some of the supporting parts / components in the overall arrangement of jigs and fixtures.